2012
DOI: 10.1089/gtmb.2012.0156
|View full text |Cite
|
Sign up to set email alerts
|

Association Between FourResistinPolymorphisms, Obesity, and Metabolic Syndrome Parameters in Tunisian Volunteers

Abstract: Resistin is an adipocyte-secreted cytokine recently discovered and has been proposed as a link between obesity and diabetes. Many resistin gene polymorphisms were described and their implication in obesity and metabolic syndrome (MetS) was controversial. Our aim was to study the relationship between four resistin polymorphisms (420C/G, 44G/A, 62G/A, and 394C/G), MetS parameters, and the risk of obesity in Tunisian volunteers. We recruited 169 nonobese (sex ratio=0.594; mean age=43.25±13.12 years; mean body mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 50 publications
3
18
0
2
Order By: Relevance
“…As discussed previously, we have not found studies analyzing the effect of resistin polymorphisms in lipid profile in children. The studies in adults have reported inconsistent results [6,17,19,22,25,27,36,37]. The study by Hivert et al [23] analyzing the association of the rs10401670SNP with diabetes-related traits in the Framingham Offspring Study did not include the relationship of the polymorphism with lipid variables in its analysis.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed previously, we have not found studies analyzing the effect of resistin polymorphisms in lipid profile in children. The studies in adults have reported inconsistent results [6,17,19,22,25,27,36,37]. The study by Hivert et al [23] analyzing the association of the rs10401670SNP with diabetes-related traits in the Framingham Offspring Study did not include the relationship of the polymorphism with lipid variables in its analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, two studies, conducted in Asians [8] and Africans [9] population have shown an increased risk of developing T2D related to the g.-420C>G mutation. Furthermore, two other African studies detected a 2.22 and 3.06-fold increased risks of developing obesity among carriers of the g.-420G allele [25,26].…”
Section: T2d Is a Leading Cause Of Morbidity And Mortality Among Adultsmentioning
confidence: 90%
“…Solaleh and Motawi found in Asians and Africans [9,8], an augmented risk of developing T2D was associated with the g.-420C>G polymorphism, whereas Chi and Chen found in Asia and Northern America no risk [23,24]. In the same manner, in Africans there was a positive association between obesity and the g.-420C>G polymorphism [25,26]; whereas, Apasalamy failed to observe any change in risk [19]. Therefore, the exact effect the g.-420C>G polymorphism has toward T2D and obesity development remains inconsistent, especially in regard to ethnicity.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Likewise, although the ENPP1-rs1044498 was associated with obesity in Moroccans, no significant association was observed among South Africans [116] . However, the RETNrs1862513 and rs3745367 have been found to be positively associated with obesity risk among several African populations [117,118] .…”
Section: Obesitymentioning
confidence: 95%